Shouhui Tongbian Capsule ameliorates 5-fluorouracil induced constipation in mice by modulating gut microbiota and activating PI3K/AKT/AQP3 signaling pathway - Zhang, Yawei; Dong, Yang; Sun, Chenghong; Zhang, Lufan; Zhang, Yi; Wang, Dan; Chen, Qian; Yao, Jingchun; Wu, Yuzheng; Wang, Tao (Frontiers in Microbiology, 2025)
ObjectiveShouhui Tongbian Capsule (SHTC) has been clinically applied to treat various types of constipation, including chemotherapy-induced constipation. However, the pharmacological mechanism by which it regulates intestinal peristalsis and treats constipation is unclear. In this study, we aimed to investigate the underlying mechanism of SHTC on chemotherapy-induced constipation through regulating of gut microbiota and PI3K/AKT/AQP3 signaling pathway.MethodsChemotherapy-induced constipation was induced with 5-Fluorouracil in C57BL/6 mice. SHTC was administrated with different dosages (100, 200, 400 mg/kg) for 12 days. The intestinal tissues were collected for the measurements of intestinal propulsion rate, time of first black stool, and expressions of colonic aquaporin. 16S rRNA sequencing, short-chain fatty acids (SCFAs) profiling, and fecal microbiota transplantation (FMT) were performed to confirm whether gut microbiota is a key target for SHTC. Finally, the expressions of proteins or genes related to PI3K/AKT/AQP3 pathway were detected.ResultsSHTC markedly improved the pathological manifestations associated with constipation and restored the deregulated gut microbiota. The mice that were given fecal supernatant from SHTC-treated mice showed significant improvement in constipation symptoms. Additionally, SHTC increased the level of acetic acid and upregulated the expression of AQP3, with activation of PI3K/AKT. Furthermore, the blockade of PI3K reversed the beneficial effect of acetic acid on the expression of AQP3.ConclusionOur findings indicated that SHTC effectively relieved 5-FU-induced constipation in mice, mainly by regulating homeostasis of gut microbiota and activating PI3K/AKT/AQP3 pathway, making it a potential protective agent against chemotherapy-induced constipation.